Long-term effects of COVID-19 in diabetic and non-diabetic patients - Ricardo Wesley Alberca; Yasmim Álefe Leuzzi Ramos; Nátalli Zanete Pereira; Danielle Rosa Beserra; Anna Cláudia Calvielli Castelo Branco; Raquel Leão Orfali; Valeria Aoki; Alberto Jose da Silva Duarte; Maria Notomi Sato (Frontiers Media S.A., 2022)
The literature presents several reports of the impact of glycemic control and diabetes in the inflammatory and coagulatory response during coronavirus disease 2019 (COVID-19). Nevertheless, the long-term impact of the COVID-19 in diabetic patients is still to be explored. Therefore, we recruited 128 patients and performed a longitudinal analysis on COVID-19-associated biomarkers of patients with COVID-19, tree and 6 months after COVID-19 recovery and put into perspective the possible long-term complication generated after COVID-19. In our investigation, we failed to verify any long-term modification on inflammatory biomarkers, but detected an increase in the glycemia and glycated hemoglobin in patients without any pre-existing history or diagnosis of diabetes (non-diabetic patients). Although diabetic and non-diabetic patients presented elevated levels of glycated hemoglobin, the c-peptide test indicated a normal beta cell function in all patients.